Laboratory evaluation of oral fluid for syphilis screening among clinic users from Lima, Peru - Jazmin Qquellon; Silver K. Vargas; Francesca Vasquez; E. Michael Reyes-Diaz; Kelika A. Konda; Carlos F. Caceres; Jeffrey D. Klausner (Microbiology Spectrum)
ABSTRACT Serological tests for syphilis require equipment unavailable in many health centers; however, point-of-care testing facilitates rapid screening using finger-prick whole blood samples. A further improvement could be oral fluid for ease of use. We evaluated the performance of treponemal antibody point-of-care testing for syphilis screening using oral fluid samples. We recruited users of STI clinics in Lima, Peru. We collected oral fluid using the OraSure collection device (OraSure Technologies Inc., USA) according to the manufacturer’s instructions and serum from each participant. Oral fluid and serum were analyzed using the SD Bioline Syphilis 3.0 rapid test (Standard Diagnostics Inc., Korea). Serum was also tested using RPR (RPR slide test, Wiener Laboratorios SAIC, Argentina) and TPPA (Serodia, Fujirebio Diagnostics Inc., Japan). We assessed oral fluid rapid test overall percent agreement, sensitivity, specificity, and Kappa coefficient against serum SD Bioline Syphilis, TPPA, and RPR. Among 323 participants, nearly half (51.3%) reported prior syphilis. The overall percent agreement, sensitivity, specificity, and Kappa coefficient of oral fluid were 71.0% (95% CI: 65.6%–75.8%), 78.1% (71.1%–83.7%), 63.5% (55.8%–70.6%), and 0.42% (0.32%–0.52%), respectively, versus serum SD Bioline Syphilis. A similar performance was obtained versus serum TPPA. When limiting the sample to TPPA-reactive with RPR titer ≥1:8, the sensitivity increased to 88.1% (75.0%–94.8%), whereas the specificity did not vary (65.3% [57.2%–72.6%]). We observed a good performance of the rapid treponemal test using oral fluid. Further investigations are needed to improve the specificity of oral fluid as a potential sample for accurate syphilis screening.IMPORTANCEPoint-of-care tests are essential for rapid and efficient screening of syphilis, especially in low-resource settings. Oral fluid specimens offer a noninvasive, accessible, and practical alternative to traditional blood samples. Our study evaluated the performance of a rapid treponemal test using oral fluid specimens. We found that the rapid treponemal test using oral fluid had good sensitivity compared with the rapid treponemal test using serum and the non-treponemal RPR test. This suggests that oral fluid could be a viable option for syphilis screening, facilitating broader and faster access to diagnosis and treatment. However, further studies are needed to improve the specificity of this method to ensure accurate screening in diverse clinical scenarios.